PENGARUH INSENTIF, TIME PRESSURE, PENGALAMAN AUDITOR, DAN LOCUS OF CONTROL TERHADAP AUDIT JUDGMENT - Synthia Ariani; Hasnawati Zainal (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2018)
The study aimed to get empirical evidence about the influence of incentives, time pressure, auditor experience, and locus of control on audit judgment. This study used convenience sampling technique. We distributed questionnair to130 auditors that work in twenty public accounting firms in DKI Jakarta. All of the firms are listed in Indonesian Institute of Certified Public Accountants. Structural Equation Modeling (SEM) was used to analysis data with AMOS 24. This research found that incentives, experience, and locus of control has positive and significant influence on audit judgment has negative and significant effect on audit judgment.